2019
DOI: 10.3390/hydrology6020034
|View full text |Cite
|
Sign up to set email alerts
|

Tree-Ring Reconstructions of Streamflow for the Tennessee Valley

Abstract: This study reports the preliminary results from a statistical screening of tree-ring width records from the International Tree-Ring Data Bank (ITRDB), to evaluate the strength of the hydrological signal, in dendrochronological records from the Tennessee Valley. We used United States Geological Survey (USGS) streamflow data from 11 gages, within the Tennessee Valley, and regional tree-ring chronologies, to analyze the dendroclimatic potential of the region, and create seasonal flow reconstructions. Prescreening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 23 publications
0
8
0
2
Order By: Relevance
“…Pederson et al (2012) reconstructed PDSI for the Apalachicola-Chattahoochee-Flint River Basin to examine early 21st century droughts, finding recent droughts were not atypical. Harley et al (2017) reconstructed streamflow for the Suwanee River in Florida, finding that historic variations exceeded current instrumental values, while Anderson et al (2019) found mixed results when comparing current flow extremes in their longterm reconstructions of rivers in the Tennessee Valley. These studies provide context to examine hydroclimate and demonstrate that current changes are not unusual when placed in a multi-century context.…”
Section: Discussionmentioning
confidence: 99%
“…Pederson et al (2012) reconstructed PDSI for the Apalachicola-Chattahoochee-Flint River Basin to examine early 21st century droughts, finding recent droughts were not atypical. Harley et al (2017) reconstructed streamflow for the Suwanee River in Florida, finding that historic variations exceeded current instrumental values, while Anderson et al (2019) found mixed results when comparing current flow extremes in their longterm reconstructions of rivers in the Tennessee Valley. These studies provide context to examine hydroclimate and demonstrate that current changes are not unusual when placed in a multi-century context.…”
Section: Discussionmentioning
confidence: 99%
“…La integración de una red de series dendrocronológicas compuesta por diversas especies ha permitido analizar en diversas regiones geográficas del continente la reconstrucción de índices de sequía (Cook et al, 2010;Stahle et al, 2016), índices de ENSO (Stahle et al, 1998) y de flujos en amplias regiones de Norteamérica (Woodhouse et al, 2006;Anderson et al, 2019) y de México (Villanueva et al, 2017;Martínez-Sifuentes et al, 2020). La cronología regional de madera temprana registró una asociación significativa con los volúmenes acumulados del período enero-junio; esto indica que la precipitación ocurrida en las estaciones de invierno, primavera y principios de verano, de la cual dependen los volúmenes escurridos, define el crecimiento de la madera temprana en el occidente de México.…”
Section: 21unclassified
“…While dendrochronological reconstructions of hydroclimate, including streamflow, have been widely utilized in the western United States (US) due to the arid, moisturelimited environment [6,7,[16][17][18][19][20][21][22][23][24][25][26][27][28], until recently, similar studies have been relatively limited in the southeastern US [3,8,14,[29][30][31][32][33][34]. However, Crockett et al [2] established TRCs to be useful and statistically significant proxies even in the humid subtropical climate of northern Florida.…”
Section: Introductionmentioning
confidence: 99%